Investigating the measurement of Malay version of inventory of dimensions of emerging adulthood (M-IDEA) among first year university students in Malaysia - Walton Wider; Ferlis Bullare@Bahari; Mazni Mustafa; Murnizam Halik (2016)
This research aimed to investigate the measurement of the Inventory of Dimensions of Emerging Adulthood (IDEA). The IDEA consisted of 28 items that were used to assess five experiences of emerging adulthood (Identity Exploration, Negativity/Instability, Feeling “In-Between”,Experimentation /Possibilities, Self-Focus). Statistical technique using Exploratory Factor Analyses (EFA) was conducted by using the IBM Statistical Package for Social Sciences (SPSS) Version 21.0, followed by Confirmatory Factor Analyses (CFA) via Structural Equation Modelling (SEM) to confirm the measurement model. EFA results revealed three factors and CFA results confirmed the correlations between the three factors (Identity Exploration/Feeling “in-between”, Negativity/Instability,Experimentation/Possibilities) were all significant, respectively. The new Malay version of IDEA (M-IDEA) has only three subscales with a total of 10 items. This study contributes to the emerging adulthood literatures by adapting the IDEA into a non-western culture - Malaysia.